Assessment of Nutritional Status between Children with Autism Spectrum Disorder and Normal Children of Bangladesh - Sohel, Md Ibrahim; Md Ashrafuzzaman, -; Acharjee, Panchanan; Epsi, Effat Zerin; Ullah, Hadi Md Habib (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background : Autism is one of the fastest spreading neuro-developmental disorders in the worldwide.Children with Autism spectrum disorder may be risk of suboptimal development which leads to increases morbidity, poor physical activity and performances. The aim of present study was to compare nutritional status between children with Autism spectrum disorder and normal children of Bangladesh. Materials and methods: It was cross-sectional and observational study. The study population was Group A consists of 100 normal Bangladeshi children and Group B consists of 100 Bangladeshi children with Autism spectrum disorder, aged between 02 and 18 years collected by convenient sampling. Height, weight, triceps skin fold thickness, suprailiac skin fold thickness and Body Mass Index (BMI) were analyzed. Results: Children with autism spectrum disorder had statistically significant lower height and weight; thicker triceps and suprailiac skin fold, were mostly under weight as compared to normal children. Conclusion: The results of this study provide the baseline information about nutritional status of normal children and children with autism spectrum disorder in Bangladesh which will help to monitor nutritional growth of children. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 55-59